Improvement Tools for Responsibility Skills of Students in the "Pedagogy" and "Psychology" Education Tracks in a Digital Learning Environment - Gulamov Jasur Baxodirovich (European International Journal of Pedagogics, 2025)
This article discusses the tools for improving responsibility skills of students in the "Pedagogy" and "Psychology" education tracks in a digital learning environment. The functions for determining the improvement of students' responsibility skills are analyzed.